ONE MECHANISM OF VERTICAL MOTIONS OF THE LITHOSPHERE - Mukhamediyev Sh.A. (My University, 1989)
The author investigates vertical motions of the lithosphere (L) resulting from a complicated injection of melt from the underlying asthenosphere. The kinematics of the process is illustrated. The complete system of equations describing the lithospheric deformations can be obtained if we fix the relationships governing the properties of the lithosphere. This system of relationships which is solved together with the problem of the quasistatics of the melt in the dike, and may be complemented by the criterion for the development of an intrusion, makes it possible to analyze different variants of injection and their consequences. The above mechanism describes in the unified way the uplift and subsidence of the surface of the lithosphere L, and also explains the irregular, intermittent nature of vertical motions, which are characteristic (among others) of certain regions of neotectonic activity. It is quite obvious that the displacements described here are augmented by the displacements induced by changes in volume of the lithosphere resulting form its heating (which accompanies the injection of melt), and its heating (which accompanies the injection of melt), and its subsequent cooling.